Adverse childhood experiences: A scoping review of measures and methods. (May 2022) - Karatekin, Canan; Mason, Susan M.; Riegelman, Amy; Bakker, Caitlin; Hunt, Shanda; Gresham, Bria; Corcoran, Frederique; Barnes, Andrew
Highlights: This scoping review summarizes ACEs research between 1999 and 2019. More attention is paid to ACEs' effects than to causes, inequities, or interventions. We suggest incorporating ACEs into broader frameworks of determinants of health. Abstract: Adverse childhood experiences (ACEs) lead to excess morbidity and mortality. However, this evidence has not resulted in large-scale efforts to prevent ACEs. We conducted a scoping review of ACEs research to determine its direction and identify advancement toward solutions to prevent ACEs. The review was conducted using PRISMA guidelines. Articles were considered eligible for inclusion if they were empirical studies based on original quantitative data from humans published between 1999 and 2019 and used the term "adverse" or adversity" to refer to a construct under study or a specific measure in the methodology. After a comprehensive search across nine databases, screening of the abstracts of 3, 944 articles and the full texts of 2, 341 articles, 1, 361 empirical articles met inclusion criteria. We coded year of publication; journal name; stated study purpose (e.g., descriptive, intervention); types of adversities used to define ACEs; funding sources and declared conflicts of interest; country of the sample; and affiliation with other studies. To characterize the extent to which ACEs research focuses on ACE prevention, we then coded "narratives" reflected in research goals, with a particular focus on whether this research focuses exclusively on ACEs as the primary predictor variables, or if it integrates "upstream" social determinants of health and health inequities that may lead to ACE exposure. Thus, we coded how the elements of the stated research goals related to ACEs (e.g., predictor, mediator, moderator, and outcome variables) using the World Health Organization's framework on social determinants of health (Solar & Irwin, 2010). Finally, we coded whether protective factors were included in research designs and the level of these factors (e.g., individual vs. community), and researchers' recommendations for translating their findings to action. All variables were coded by at least two coders; inter-rater reliabilities ranged from 79 to 100%. We found that 60.6% of articles were based on samples recruited from the U.S.; funding sources have shifted to U.S. institutions with biomedical or clinical concerns; that only 47.2% of articles included in their definition of ACEs all seven items from the original ACE study; and that the dominant narrative about ACEs started with ACEs as the "villains" who begin a story of decline and ended with "victims" who have behavioral and/or emotional problems. Studies overwhelmingly examined the downstream effects of ACEs rather than upstream causes or preventive interventions. That is, only 6.6% of articles proposed protective factors that went beyond the individual or family level; and researchers' recommendations favored amelioration of ACEs after they occur, with only 20% of articles mentioning primordial or primary prevention. This disproportionate focus on downstream determinants after ACEs have already occurred limits the impact of this research in terms of potential cost-benefit, social justice, and mitigation of health inequities. We recommend that future ACEs research be incorporated into broader, strengths-based and action-oriented frameworks focused on social determinants of health and health inequities; link ACEs to their putative causes as a bridge to primordial/primary prevention; address obstacles to this shift toward upstream causes of ACEs; and communicate findings and recommendations more effectively.